An Analysis of Aspirated Allophones Produced by UINSU Students in English Pronunciation - Nahdiyah Rizqoh; Putri Humaira; Queen Latifa Dalimunthe; Yani Lubis (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Pronunciation is an essential component of language learning because it influences intelligibility and communication effectiveness. One important feature of English pronunciation is aspiration, which occurs in the voiceless stop consonants /p/, /t/, and /k/ under specific phonological conditions. This study aims to analyze how UINSU students produce aspirated allophones in English pronunciation and identify factors influencing their production. This research employed a qualitative descriptive approach involving three students from the English Education Study Program at UINSU. Data were collected through interviews and voice-note recordings. The findings indicate that students generally understand the concept of aspiration and can apply it in appropriate phonological environments. However, their production remains inconsistent, particularly during spontaneous speech. Several factors influencing students’ pronunciation include first-language transfer, limited pronunciation practice, phonological awareness, and classroom instruction. The study concludes that although students have developed awareness of English aspiration, more explicit pronunciation training is necessary to achieve consistent and accurate production.